4x+8-x+3=2x+23

Simple and best practice solution for 4x+8-x+3=2x+23 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4x+8-x+3=2x+23 equation:


Simplifying
4x + 8 + -1x + 3 = 2x + 23

Reorder the terms:
8 + 3 + 4x + -1x = 2x + 23

Combine like terms: 8 + 3 = 11
11 + 4x + -1x = 2x + 23

Combine like terms: 4x + -1x = 3x
11 + 3x = 2x + 23

Reorder the terms:
11 + 3x = 23 + 2x

Solving
11 + 3x = 23 + 2x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-2x' to each side of the equation.
11 + 3x + -2x = 23 + 2x + -2x

Combine like terms: 3x + -2x = 1x
11 + 1x = 23 + 2x + -2x

Combine like terms: 2x + -2x = 0
11 + 1x = 23 + 0
11 + 1x = 23

Add '-11' to each side of the equation.
11 + -11 + 1x = 23 + -11

Combine like terms: 11 + -11 = 0
0 + 1x = 23 + -11
1x = 23 + -11

Combine like terms: 23 + -11 = 12
1x = 12

Divide each side by '1'.
x = 12

Simplifying
x = 12

See similar equations:

| y^2+3y+yx+3x=0 | | 10x-37=-87 | | x=8-3x | | (x-8)=4 | | (X*0.1)+X=100 | | (100*0.1)+100=X | | X*0.1=100 | | 6x+11=2x-1 | | (-3)(3+2x)+4x^2+1(1-x)=-11 | | 18x-x^2=71 | | 3x-15y=0 | | 2a+11=15 | | 36*(25+48)-16*22= | | 2x+36=6x+3 | | 7+5x=42 | | H=-4.9t^2+80t | | 1+3x=16-2x | | 5a^2+22a+21=0 | | 2x+8=3x+6+8 | | 2y^2+19y=-24 | | x^3-15x^2+800=0 | | 6-8x=47-15x | | 4v-5=v+4 | | (x)(x+1)=14(2x+1)+44 | | x+786(y+z)=2526 | | 129-4x=4x+9 | | -6-4x=15-9x | | x+3x-3= | | x+2y=128 | | 2x-3x+1+8x=2x+5+4x-3 | | (x-5)(x).5=42 | | 6-8x=3-9x |

Equations solver categories